Interprofessional Collaborative Care: Addressing Oral-Systemic Health Connections - Patricia B. Bonwell; Sharon K. Lanning; S. Esra Sahingur; Gerald F. Clarke; Jeffrey R. Lodge; Samuel L. Malkinson; John A. Svirsky (Association of American Medical Colleges, 2013)
Abstract Evidence suggests an oral-systemic link between periodontal disease cardiovascular disease, diabetes, and birth outcomes. Increased awareness of oral-systemic links will support the important relevance for addressing oral health in patients as it impacts and is impacted by overall health. By focusing on these links and the utilization of risk assessments, this module builds relevance for health care providers in addressing the oral systemic relationships with their patients. A three pronged approach will be utilized to support the integration of this free standing oral health module into medical educational curricula: instruction on oral-systemic relationships, assessment of the patient's oral health in medical setting, and interdisciplinary management of the patient. Using a mixed media design, the module was packaged together using the Softchalk Program, and incorporates video presentations into the lecture segment as supplemental material. The majority of didactic content will be given as recorded lectures. Video presentations of reenactments depicting the performance of an oral screening accompanied by a questionnaire-based periodontal assessment and utilization of referrals are included. This module is both learner and patient focused. It will function as a full, stand-alone teaching/learning and assessment activity. The content is relevant and can be inserted into medical school curricula where content experts may not be readily available. The target audience for this module includes those practicing in the primary care setting. This may include pre- and postdoctoral students in dentistry, medicine, nursing, and pharmacy as well as clinicians from these disciplines practicing outside of the formal educational training setting. This module is innovative in that it will enable module participants, as practitioners, to perform periodontal risk assessments to supplement overall health evaluations and aid in making proper referrals.